KARAKTERISIK LUARAN BAYI YANG LAHIR DENGAN SECTIO CAESAREA DI RSUP SANGLAH DENPASAR - Hendry Raymen Satria; I Made Kardana; I GAN Sugitha Adnyana (Universitas Udayana, 2020)
Researches about the health effect of caesarean section (CS) on maternal and perinatal morbidity, pediatric outcomes, psychologic or social well-being are still unclear and limited. This research aims to study the characteristics outcome and indications of CS baby in Sanglah General Hospital. The descriptive cross-sectional research was conducted on 36 eligible babies out of 72 cesarean cases by medical record throughout 2017. As a result, 22 (61.1%) were male, 18 (50%) were preterm, 19 (52.8%) were normal weight baby. Four most common indications found were antepartum bleeding placenta previa, fetal distress, breech presentation and locus minoris resitentiae (LMR) with 3 (8.3%) cases each. In conclusion, CS delivery rate were higher in male gender. Proportion of baby between aterm and preterm, also normal and low birth weight were similar. Placenta previa, fetal distress, breech presentation and LMR as the most common indication for cesarean babies in Sanglah General Hospital. Keywords: Cesarean Section, Characteristics, Indication, Neonatal, Pediatrics Outcome